GE_GERICHTE P/19973/2025 vom 29. September 2025 - GE Cour de justice (2025)
ENSEIGNEMENT;DIFFAMATION;CALOMNIE;DROIT DE LA FONCTION PUBLIQUE;RÉSILIATION;ABUS D'AUTORITÉ | CPP.310; CP.173; CP.174; CP.177; CP.14; CP.312